Exploring frailty in Brazil: an analysis of the ELSI-Brazil survey - Henrique Pott Junior; Mario Ulises Pérez-Zepeda; Melissa K. Andrew; Kenneth Rockwood (Cadernos de Saúde Pública)
Abstract: The Brazilian aging population will challenge publicly funded health services, on which most Brazilians rely. The country must prepare for aging-associated health challenges such as frailty. We used data from the Brazilian Longitudinal Study of Aging (ELSI-Brazil) to generate a standardized Frailty Index (FI), assess frailty levels among this population, and supply reliable and nationwide information. In total, 9,901 adults aged 50 years or older were studied in the second wave of ELSI-Brazil. A 53-item FI was created according to a standardized protocol. Logistic regression was used to determine the association between frailty levels and disability/health status, whereas the relationship between frailty level, disabilities, and healthcare use was analyzed by a negative binomial regression. Frailty was high, with a 0.19 weighted mean FI score and 0.19 median. Frailty distribution was right-skewed, with higher levels in women and increased exponentially with age. Widow(er)s, black and mixed-race individuals, and those living in rural areas had higher levels of frailty. Regression models showed that higher frailty was associated with poorer self-assessment of health, higher disability, and greater use of healthcare services. This study shows a high prevalence of frailty in Brazilian middle-aged and older adults and its association with disability, health status, and healthcare service use. These relevant findings can inform healthcare policies and design services prioritizing this population’s health, particularly for those using public healthcare.